A STUDY ON ASSESSING HANDLOOM WEAVER’S STATUS DURING COVID-19 SITUATION IN TAMIL NADU - M S, Sasikala; K, Shaila (The journal of contemporary issues in business and government, 2021)
Clothing is considered to be evergreen until human being resides in this universe. Diversified apparels reveal the status of the people socially and economically. In today’s scenario, large number of people spends on their dressing which looks elegant, pretty, sparkling etc., One fact is hidden here about the weavers who brings out all these outcomes. As it is quite transparent that, in ancient days 3 occupations are considered to be major i.e. Food, Clothing and Shelter. To be focused on these 3 professions, Food is considered to be prime which is offered by Farmers, then comes clothing. Post Adam-Eve period, once human beings learned to behave in civilized manner, clothing plays honor part which is offered by weavers. Then to reside with safety and security, home/house is required which is offered by Mason. In this article, Researcher tried to dig on how the weavers are empowered currently which have reflection in economic development too. It is important to know about weaver’s contribution and the level of empowerment attained as the product from handloom industry has greater demand. Even many shifted to modern lives and wears, still unique place is there for traditional wear too which is to be acceptable without any hesitation.